2021
DOI: 10.4081/ejtm.2021.9783
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine platform COVIDREHAB for remote rehabilitation of patients after COVID-19

Abstract: The world's practice has shown the importance of medical rehabilitation, which allows increasing the effectiveness of treatment of patients with COVID-19, and also significantly reduce the risks of developing complications after COVID-19. Moreover, timely medical rehabilitation reduces the frequency of disability retirement. We developed and investigated the effectiveness of the telemedicine platform “COVIDREHAB” in order to enhance the effectiveness of the recovery period during self-isolation, as well as to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
4
17
0
Order By: Relevance
“…Twenty-seven of the studies involved mobile apps, web pages, or virtual platforms accessed using a laptop, tablet or smartphone. 39 , 41 44 , 46 , 47 , 49 , 55 , 59 61 , 63 69 , 71 , 72 , 74 76 , 79 81 In two studies the intervention was delivered using a teleconference platform, 66 , 76 and one social platform. 67 Other transmitting devices/systems used in the studies included the health buddy device, 40 , 51 the iRobi robot, 73 a PalmOne, 45 touch screen telemonitoring equipment, 57 a home health system connected to a phone line, 53 a computer-linked interactive phone tele-system, 48 a tele-modem, 50 , 54 , 62 , 82 a satellite platform, 83 computer or push-bottom telephone, 58 handheld monitor connected to a phone line, 52 a digital pen and health dairy paper together with SMS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-seven of the studies involved mobile apps, web pages, or virtual platforms accessed using a laptop, tablet or smartphone. 39 , 41 44 , 46 , 47 , 49 , 55 , 59 61 , 63 69 , 71 , 72 , 74 76 , 79 81 In two studies the intervention was delivered using a teleconference platform, 66 , 76 and one social platform. 67 Other transmitting devices/systems used in the studies included the health buddy device, 40 , 51 the iRobi robot, 73 a PalmOne, 45 touch screen telemonitoring equipment, 57 a home health system connected to a phone line, 53 a computer-linked interactive phone tele-system, 48 a tele-modem, 50 , 54 , 62 , 82 a satellite platform, 83 computer or push-bottom telephone, 58 handheld monitor connected to a phone line, 52 a digital pen and health dairy paper together with SMS.…”
Section: Resultsmentioning
confidence: 99%
“…Overall well-being improved in 83% of COVID-19 patients who participated in an intervention involving telerehabilitation and telemonitoring 75 ( Table 3 ). Telemonitoring interventions were associated with an improvement in HRQoL in patients with asthma 42 , 45 , 58 , 61 , 63 and COPD (4 of 6 studies), 46 , 49 , 51 , 60 and no changes in HRQoL were identified in one study that included both asthma and COPD patients combined.…”
Section: Resultsmentioning
confidence: 99%
“…116 A detailed neurological and muscular evaluation is also essential because many ICU-AW patients with COVID-19 may have early deficits. 146 If the long-term physical consequences of COVID-19 on skeletal muscle are added to the effects of ICU-AW, [147][148][149][150][151][152][153][154][155][156] recovery is complex, along with the high health care costs that this entails. 117 It is crucial to start a nutritional intervention and preventive physical and respiratory therapy to delay the accelerated loss of skeletal muscle mass and maintain respiratory function during the ICU stay.…”
Section: Discussionmentioning
confidence: 99%
“…96 Non-controlled studies and those in populations without continuous symptoms in line with our definition of Long COVID, suggest that pulmonary rehabilitation techniques are beneficial in patients who have experienced COVID-19. 26,27,30,38,43,47,53,54,56,59,60,63,66,70,78,85 Pulmonary rehabilitation is likely to benefit those experiencing dyspnoea following COVID-19 but further trial evidence is needed to support the appropriateness, effectiveness and cost-effectiveness in those with symptoms lasting at least 12 weeks. Such evidence might be provided by ongoing RCTs designed for this purpose, such as the Rehabilitation Exercise and Psychological Support after COVID-19 Infection (REGAIN)trial which is evaluating the effectiveness of a rehabilitation programme for adults with ongoing COVID-19 sequelae for more than three months after hospital discharge.…”
Section: Discussionmentioning
confidence: 99%